EVALUASI AKSESIBILITAS BAGI PENYANDANG DISABILITAS PADA GEDUNG RSUD DR. M. HAULUSSY KOTA AMBON - Randy Pratama Putra; Buyang, C. G.; Taihuttu, Felix (JURNAL SIMETRIK, 2025)
Persons with disabilities have the same right to access facilities and infrastructure without discrimination, including public service facilities such as hospitals. This study aims to evaluate the level of accessibility compliance for persons with disabilities at RSUD Dr. M. Haulussy, Ambon City, based on the Regulation of the Minister of Public Works and Public Housing (Permen PUPR) No.14/PRT/M/2017. The research employed direct observation and measurement methods to assess the feasibility of existing facilities and infrastructure related to accessibility for persons with disabilities. The measurement data were compared with the standards stipulated in Permen PUPR No.14/PRT/M/2017. The compliance levels found were: doors 63.64%, corridors 100.00%, stairs 62.50%, ramps 80.00%, toilets 46.66%, and washbasins the lowest compliance at 25.00%. Based on the evaluation, the overall accessibility compliance of RSUD Dr. M. Haulussy was 62.97%, according to the technical requirements set out in Permen PUPR No.14/PRT/M/2017 concerning building accessibility requirements.Keywords: Accessibility, People with Disabilities, Hospitals